Efficacy and Safety of Coronary Intervention Via Distal Trans-Radial Access (DTRA) in Patients with Low Body Mass Index - Muhammad Aslam, Ijaz Ahmad, Sarfraz Ali Mangi, Khair Ul Bashar, Muhammad Kamran Khan, Dildar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The distal transradial approach (dTRA) is anticipated to improve the benefits of transradial availability, hemorrhagic incidents and the occurrence of radial artery occlusion (RAO) with the dTRA is uncertain. The aim of this study to investigate the puncture time rate, homeostasis and radial artery occlusion related to low BMI in distal artery access (dTRA) vs conventional radial artery access (cTRA). Study design: This cross-sectional study was carried out at NICVD, Nawabshah, for the duration of six months from July 2022 to December 2022. Materials and Methods: The total participants were 160 who diagnosed coronary artery disorder and include 75 participants in dTRA and 85 participants in cTRA. The age group were included >21 years. The demographic data, surgical methods, catheterization, procedure-related data, procedures of puncture, ultrasound follow up and BMI were recorded. All data was analyzed by SPSS 22 version. Results: The mean age of participants in dTRA group was 72.0±10.1 years and cTRA group was 73.0±18.0 years. In gender, age and BMI were non-significant in both groups. The crossover rate, puncture time, one needle puncture rate and radial artery occlusion were shown significantly change in dTRA and cTRA group, p=0.005. Conclusion: Distal radial access is a new facility for cardiovascular interventions that provides several benefits over prior links. The key benefits would be less arterial blockage and faster hemostasis. When compared to traditional radial artery access, the dTRA may be a viable and reliable connectivity site for both diagnostic and interventional coronary methods, with a decreased prevalence of RAO, high crossover rate and time needed for hemostasis. Keywords: Distal transradial artery (dTRA); conventional transradial artery (cTRA); Radial artery occlusion (RAO)